Positive electrode materials, positive electrode sheets, lithium secondary batteries, battery modules, battery packs and devices

By using the positive electrode material of lithium iron phosphate single crystal particles and secondary particles, the problems of low energy density and poor processing performance of lithium iron phosphate batteries are solved, and a lithium-ion battery with high energy density, long cycle life and low cost are achieved.

CN116097468BActive Publication Date: 2025-04-01CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202080104510.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-09-03
Publication Date
2025-04-01
Estimated Expiration
2040-09-03

AI Technical Summary

Technical Problem

The voltage platform, capacity and compaction density of the lithium iron phosphate battery are low, resulting in unsatisfactory energy density, and the problem of cold pressing strip breaking or film removal is prone to occur during the manufacturing process.

Method used

Using a positive electrode material containing lithium iron phosphate single crystal particles and secondary particles, the compaction density and processing performance of the electrode sheet are improved and the overall cost of the battery cell is reduced through the low specific surface area of ​​lithium iron phosphate secondary particles and the full filling of lithium iron phosphate single crystal particles.

Benefits of technology

It significantly improves the energy density of lithium-ion batteries, enhances the flexibility and crack resistance of the electrode sheet, reduces the cost of the battery cell, and improves the cycling and dynamic performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116097468B_ABST
    Figure CN116097468B_ABST
Patent Text Reader

Abstract

The present application relates to a positive electrode material, a positive electrode sheet, a lithium secondary battery, a battery module, a battery pack and a device. The positive electrode material involved in the present application comprises lithium iron phosphate single crystal particles and lithium iron phosphate secondary particles. Among them, the lithium iron phosphate secondary particles have a low specific surface area, which can reduce the consumption of binders and solvents in the pulping process, increase the solid content of the slurry, and improve the processing performance of thick coated pole pieces. At the same time, the lithium iron phosphate single crystal is fully filled into the particle gaps of the lithium iron phosphate secondary particles, which can further increase the compaction density of the pole piece and reduce the membrane resistance of the positive electrode sheet, thereby improving the gram capacity and cycle performance of the lithium secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular, to a positive electrode material, a positive electrode sheet, a lithium secondary battery, a battery module, a battery pack and a device. Background Art

[0002] As a positive electrode material for lithium-ion batteries, lithium iron phosphate has advantages in safety, cycle performance and cost, and is widely used in buses, passenger cars and large-scale energy storage. However, the voltage platform, capacity performance and pole compaction density of lithium iron phosphate full batteries are all at a low level. Therefore, compared with ternary positive electrode material batteries, the energy density of lithium iron phosphate batteries is not satisfactory.

[0003] Through the calculation of battery cell design, it can be found that increasing the coating weight per unit area of ​​the active material of the positive electrode sheet, that is, the mass surface density of the active material, can significantly improve the energy density of lithium-ion batteries, while increasing the use efficiency of other materials (current collector, shell, electrolyte and separator) and reducing the overall cost of the battery cell. However, when the positive electrode material in the lithium-ion battery is lithium iron phosphate, the positive electrode sheet is very likely to break or peel off due to cold pressing during the actual manufacturing process or use, making it difficult to achieve high energy density.

[0004] Therefore, how to prepare lithium-ion batteries that are compatible with high safety, long cycle and high energy density has become a difficult problem that the industry urgently needs to overcome. Summary of the invention

[0005] In view of the problems existing in the background technology, the present application provides a positive electrode material, a positive electrode plate, a lithium secondary battery, a battery module, a battery pack and a device.

[0006] In a first aspect, the present application provides a positive electrode material, which comprises a first positive electrode active material represented by formula (I) and a second positive electrode active material represented by formula (II).

[0007] LiFe 1-x1 M1 x1 PO4(I)

[0008] LiFe 1-x2 M2 x2 PO4(II)

[0009] Among them, 0≤x1≤0.1, 0≤x2≤0.1; M1 and M2 are each independently selected from at least one of Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr or Ti; the first positive electrode active material is a single crystal particle, and the second positive electrode active material is a secondary particle.

[0010] Compared with the prior art, this application has at least the following advantages:

[0011] The positive electrode material provided in the present application comprises a first positive electrode active material and a second positive electrode active material, wherein the first positive electrode active material is a lithium iron phosphate single crystal particle, and the second positive electrode active material is a lithium iron phosphate secondary particle. Among them, the lithium iron phosphate secondary particle has a low specific surface area, which can reduce the consumption of binder and solvent in the pulping process and increase the solid content of the slurry. The increase in the solid content of the slurry can reduce the processing difficulty of the thick coated pole piece: when the active material layer of the thick coated pole piece is dried, the volatilization amount of the dispersed solvent is reduced, the volume strain of the membrane layer is reduced, and the segregation effect of the binder in the direction perpendicular to the pole piece surface is suppressed, and the pole piece is not prone to powder loss, cracking, and demolding. At the same time, the lithium iron phosphate single crystal particles are fully filled into the particle gaps of the lithium iron phosphate secondary particles, increasing the bonding force between the lithium iron phosphate secondary particles, and further improving the compaction density of the pole piece; it can also improve the flatness of the contact surface between the active material and the current collector, which helps to slow down the damage of the lithium iron phosphate secondary particles to the current collector surface during the cold pressing process of the pole piece, strengthen the flexibility of the pole piece, and reduce the probability of the pole piece breaking during the processing. In addition, since the production cost of lithium iron phosphate secondary particles is relatively low, the technical solution of the present application can also reduce the overall cost of the battery cell.

[0012] In the positive electrode material provided in the present application, the secondary particles are pomegranate-like in shape formed by the agglomeration of multiple primary particles. Optionally, the primary particles are single crystal nanoparticles. Optionally, the average particle size d of the primary particles is in the range of 20nm-500nm. At this time, the particle size of the primary particles is in a suitable range, the side reaction rate of the positive electrode material and the electrolyte and the kinetic performance of the positive electrode of the battery are at a reasonable level, and the capacity of the battery and the cycle performance are better.

[0013] In the positive electrode material provided in the present application, the second positive electrode active material satisfies at least one of the following conditions: (1) the median particle size Dv50 of the second positive electrode active material is 2.5 μm-10.5 μm; optionally, the median particle size Dv50 of the second positive electrode active material is 4.5 μm-8.5 μm; further optionally, the median particle size Dv50 of the second positive electrode active material is 6 μm-7 μm; (2) the specific surface area of ​​the second positive electrode active material is 3.5 m 2 / g-10.5m 2 / g, optionally, the specific surface area of ​​the second positive electrode active material is 5m 2 / g-9m 2 / g; Further optionally, the specific surface area of ​​the second positive electrode active material is 6.5m 2 / g-7.5m 2 / g.

[0014] When the median particle size Dv50 and specific surface area BET of the second positive electrode active material are within the range provided in this application, its particle size and specific surface area are moderate, which is conducive to the sufficiency of the first positive electrode active material filling in the gaps between its particles, so that the pole piece compaction density is high, the active material and the current collector contact layer have good flatness, and the pole piece has good processing performance. At the same time, the solid content of the positive electrode material mixed system slurry is within a suitable range, which is conducive to improving the capacity and cycle performance of the battery.

[0015] In the positive electrode material provided in the present application, the single crystal particles are independent particles with continuous internal lattices and almost no grain boundary separation.

[0016] In the positive electrode material provided in the present application, the powder resistivity of the first positive electrode active material at 12 MPa is less than 150 Ω·cm. Optionally, the powder resistivity of the first positive electrode active material at 12 MPa is less than 80 Ω·cm. Further optionally, the powder resistivity of the first positive electrode active material at 12 MPa is less than 30 Ω·cm.

[0017] As the powder resistivity of the first positive electrode active material decreases, its conductivity is improved, which is beneficial to improving the electron transmission performance between the positive electrode active materials, thereby reducing the film resistivity of the positive electrode sheet and promoting the capacity and cycle performance of the battery.

[0018] In the positive electrode material provided in the present application, the first positive electrode active material satisfies at least one of the following conditions: (1) the median particle size Dv50 of the first positive electrode active material is 0.5 μm-2.0 μm, (2) the specific surface area of ​​the first positive electrode active material is 6.0 m 2 / g-20m 2 / g.

[0019] When the median particle size Dv50 of the first positive electrode active material is within the range of 0.5μm-2.0μm, it is conducive to fully filling the gaps between the particles of the second positive electrode active material, the secondary particles of lithium iron phosphate, to better improve the compaction density of the pole piece and the processing performance of the pole piece. 2 / g-20m 2 / g range, which is beneficial to further reduce the consumption of binder in the pulping process, increase the solid content of the slurry, and ensure a larger specific surface area for electrochemical reaction activity.

[0020] In the positive electrode material provided in the present application, the mass percentage of the second positive electrode active material is greater than the mass percentage of the first positive electrode active material. Optionally, the mass percentage of the second positive electrode active material is 55%-90%; further optionally, the mass percentage of the second positive electrode active material is 60%-85%; further optionally, the mass percentage of the second positive electrode active material is 65%-80%.

[0021] In the embodiment of the present application, the second active material, lithium iron phosphate secondary particles, have a low specific surface area, which can increase the solid content of the slurry, reduce the difficulty of processing thick coated pole pieces, and reduce the production cost of positive electrode materials; and the first active material, lithium iron phosphate single crystals, are filled in the particle gaps of the lithium iron phosphate secondary particles, further increasing the compaction density of the pole piece and improving the processing performance of the pole piece. When the mass percentage of the second positive electrode active material is greater than the mass percentage of the first positive electrode active material, that is, when the mass percentage of the second positive electrode active material is greater than 50%, a positive electrode pole piece with improved performance and lower cost can be obtained. As the content of the second positive electrode active material further increases, the compaction density and processing performance of the pole piece are further improved; at the same time, an appropriate amount of the first positive electrode active material needs to be added to fill in the gaps between the lithium iron phosphate secondary particles to increase the bonding force between the lithium iron phosphate secondary particles, improve the compaction density and processing performance of the pole piece, improve the electron transmission performance and reduce the membrane resistance. When the mass percentage of the second positive electrode active material is 60%-85%; or further 65%-80%, the first positive electrode active material and the second positive electrode active material synergize with each other to improve the comprehensive processing performance of the slurry and the electrical performance of the electrode sheet.

[0022] In a second aspect, the present application provides a positive electrode plate, comprising a positive electrode active material layer, and the positive electrode active material layer contains the positive electrode material of the first aspect of the present application.

[0023] The coating weight per unit area of ​​the positive electrode sheet provided in this application is 140g / m 2 -390g / m 2 ; Optional, single-sided unit area coating weight is 190g / m 2 -320g / m 2 ; Further optionally, the coating weight per unit area on one side is 230g / m 2 -280g / m 2 .

[0024] In the positive electrode sheet provided in the present application, the limit solid content of the positive electrode slurry is increased, so that a higher coating weight and a larger coating thickness can be achieved; with the increase of coating weight and coating thickness, the battery volume utilization rate is improved, which helps to improve the energy density, but the lithium ion migration path is also longer, the diffusion impedance is increased, the lithium ion concentration polarization of the battery becomes larger during the discharge process, and the battery capacity is reduced. When the coating weight is 230g / m 2 -280g / m 2 When the battery is charged, the battery energy density and cycle performance are optimal.

[0025] The membrane resistance of the positive electrode sheet provided in the present application is less than 2000mΩ; optionally, the membrane resistance is less than 800mΩ; further optionally, the membrane resistance is less than 200mΩ. The positive electrode sheet of the present application has a lower membrane resistance, which can promote the energy density and cycle performance of the battery.

[0026] In a third aspect, the present application provides a lithium secondary battery, which includes the positive electrode sheet described in the second aspect of the present application.

[0027] In a fourth aspect, the present application provides a battery module, which includes the lithium secondary battery described in the third aspect of the present application.

[0028] In a fifth aspect, the present application provides a battery pack, which includes the battery module described in the fourth aspect of the present application.

[0029] In a sixth aspect, the present application provides a device comprising the lithium secondary battery described in the third aspect of the present application or the battery module described in the fourth aspect of the present application or the battery pack described in the fifth aspect of the present application, wherein the lithium secondary battery or the battery module or the battery pack is used as a power source or energy storage unit for the device.

[0030] Compared with traditional lithium iron phosphate materials, the positive electrode material provided by the present application has a significantly improved slurry limit solid content during the slurry making process, the cracking of the electrode sheet after thick coating is improved, the bonding force between the diaphragm and the current collector is improved, and the diaphragm resistance is reduced. The use of the positive electrode material of the present application to prepare positive electrode sheets and apply them to lithium secondary batteries can significantly improve the energy density, kinetic performance and cycle performance of lithium secondary batteries. At the same time, the device using the lithium secondary battery or battery module or battery pack of the present application as a power source or energy storage unit also has good power performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 1 is a scanning electron microscope image of the second positive electrode active material at different magnifications according to a specific embodiment of the present application: wherein the magnification of 1A is 1000X times, the magnification of 1B is 5000X times, and the magnification of 1C is 10000X times;

[0032] Figure 2 2A is a scanning electron microscope image of the first positive electrode active material at different magnifications according to a specific embodiment of the present application: wherein the magnification of 2A is 10000X times, and the magnification of 2B is 30000X times;

[0033] Figure 3 is a scanning electron microscope image of a cross section of a positive electrode according to a specific embodiment of the present application;

[0034] Figure 4 is a three-dimensional diagram of a lithium secondary battery according to a specific embodiment of the present application;

[0035] Figure 5 yes Figure 4 An exploded view of a lithium secondary battery is shown;

[0036] Figure 6 is a three-dimensional diagram of a battery module according to a specific embodiment of the present application;

[0037] Figure 7 is a three-dimensional diagram of a battery pack according to a specific embodiment of the present application;

[0038] Figure 8 yes Figure 7 An exploded view of the battery pack shown;

[0039] Fig. 9 It is a schematic diagram of a device according to a specific embodiment of the present application.

[0040] The reference numerals are described as follows:

[0041] 1 battery pack

[0042] 2 upper box

[0043] 3 lower cabinets

[0044] 4 battery modules

[0045] 5Lithium secondary battery

[0046] 51 Shell

[0047] 52 electrode assembly

[0048] 53 Top cover assembly DETAILED DESCRIPTION

[0049] The present application is further described below in conjunction with specific embodiments. It should be understood that these specific embodiments are only used to illustrate the present application and are not used to limit the scope of the present application.

[0050] Cathode Materials

[0051] The first aspect of the present application relates to a positive electrode material, which comprises a first positive electrode active material represented by formula (I) and a second positive electrode active material represented by formula (II).

[0052] LiFe 1-x1 M1 x1 PO4 (I)

[0053] LiFe 1-x2 M2 x2 PO4 (II)

[0054] Among them, 0≤x1≤0.1, 0≤x2≤0.1; M1 and M2 are each independently selected from at least one of Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr or Ti; the first positive electrode active material is a single crystal particle, and the second positive electrode active material is a secondary particle.

[0055] The inventors of the present application have found through research that in the production process of lithium iron phosphate positive electrode materials, in order to improve the capacity and kinetic performance of the positive electrode materials, they generally need to be fully nano-sized. However, the nano-sized process makes the lithium iron phosphate material have a high specific surface energy, which makes the material difficult to process. When the thickness of the positive electrode coating is thickened, the powder loss, cracking, and film peeling of the pole piece will be aggravated. At the same time, to achieve the same pole piece compaction density, the pole piece with a high surface density requires a greater cold pressing roller pressure, and the positive electrode material particles will damage the metal substrate during this process. The defects of the pole piece produced in the above-mentioned cold pressing process will cause the subsequent pole piece to break during winding and the bare battery cell during hot pressing.

[0056] The inventor of the present application has found through further research that: in the embodiment of the present application, the second positive active material, lithium iron phosphate secondary particles, have a low specific surface area, which can reduce the consumption of binders and solvents during the pulping process and increase the solid content of the slurry. The increase in the solid content of the slurry can reduce the processing difficulty of thick coated pole pieces: when the active material layer of the thick coated pole piece is dried, the volatilization amount of the dispersant is reduced, the volume strain of the membrane layer is reduced, and the segregation effect of the binder in the direction perpendicular to the pole piece surface is suppressed, and the pole piece is not prone to powder loss, cracks, and film removal. At the same time, the first positive active material, lithium iron phosphate single crystal, is fully filled into the particle gap of the lithium iron phosphate secondary particles, increasing the bonding force between the lithium iron phosphate secondary particles, and further improving the compaction density of the pole piece; it can also improve the flatness of the contact surface between the active material and the current collector, which helps to slow down the damage of the lithium iron phosphate secondary particles to the current collector surface during the cold pressing process of the pole piece, enhance the flexibility of the pole piece, and reduce the probability of pole piece breakage during processing.

[0057] In some embodiments of the present application, the lithium iron phosphate secondary particles as the second positive electrode active material are in a pomegranate-like form formed by agglomeration of multiple lithium iron phosphate primary particles. The lithium iron phosphate primary particles are the smallest structural units constituting the hierarchical structure of secondary particles, and refer to independent particles with low porosity, which can be observed by an electron microscope.

[0058] In some embodiments of the present application, the average particle size d of the primary particles is in the range of 20nm-500nm. In the present application, when the average particle size d of the primary particles is in the above range, the side reaction rate between the formed positive electrode material and the electrolyte and the kinetic performance of the positive electrode of the battery are at a reasonable level, and the capacity and cycle performance of the battery are better. The average particle size d of the primary particles is obtained by statistically analyzing the particle size of the primary particles using the long diameter statistical method. Specifically: In the SEM image, the diameters of the long axis direction of multiple primary particles are measured and the average value is taken.

[0059] In some embodiments of the present application, the lithium iron phosphate primary particles that agglomerate to form the lithium iron phosphate secondary particles are single crystal nanoparticles. Figure 1 The scanning electron microscope images of the second positive electrode active material at different magnifications are shown, wherein the magnification of 1A is 1000X times, the magnification of 1B is 5000X times, and the magnification of 1C is 10000X times.

[0060] In some embodiments of the present application, the median particle size Dv50 of the second positive electrode active material is 2.5μm-10.5μm. In some embodiments of the present application, the median particle size Dv50 of the second positive electrode active material is 4.5μm-8.5μm. In some embodiments of the present application, the median particle size Dv50 of the second positive electrode active material is 6μm-7μm. The median particle size Dv50 value means that the volume of particles with a particle size greater than and less than this value in the powder sample each accounts for 50% of the total volume.

[0061] In some embodiments of the present application, the specific surface area of ​​the second positive electrode active material is 3.5 m 2 / g-10.5m 2 In some embodiments of the present application, the specific surface area of ​​the second positive electrode active material is 5m 2 / g-9m 2 In some embodiments of the present application, the specific surface area of ​​the second positive electrode active material is 6.5 m 2 / g-7.5m 2 / g.

[0062] When the median particle size Dv50 and specific surface area BET of the second positive electrode active material are within the above range, its particle size and specific surface area are moderate, which is conducive to the full filling of the first positive electrode active material in its particle gap, so that the pole piece compaction density is high, the active material and the current collector contact layer have good flatness, and the pole piece has good processing performance. At the same time, the solid content of the positive electrode material mixed system slurry is within an appropriate range, which is conducive to the capacity and cycle performance of the battery.

[0063] In some embodiments of the present application, the lithium iron phosphate single crystal particles as the first positive electrode active material are independent lithium iron phosphate particles with continuous internal lattices and almost no grain boundary separation. Figure 2 The scanning electron microscope images of the first positive electrode active material at different magnifications are shown, wherein the magnification of 2A is 10000X times, and the magnification of 2B is 30000X times.

[0064] In some embodiments of the present application, the powder resistivity of the first positive electrode active material at 12Mpa is 150Ω·cm or less. In some embodiments of the present application, the powder resistivity of the first positive electrode active material at 12Mpa is 80Ω·cm or less. In some embodiments of the present application, the powder resistivity of the first positive electrode active material at 12Mpa is 30Ω·cm or less.

[0065] The first positive electrode active material has a low powder resistivity and a high conductivity, which is beneficial to improving the electron transmission performance between the positive electrode active materials, thereby reducing the film resistivity of the positive electrode sheet and promoting the capacity and cycle performance of the battery.

[0066] In some embodiments of the present application, the median particle size Dv50 of the first positive electrode active material is 0.5μm-2.0μm, which is conducive to its full filling into the particle gaps of the second positive electrode active material secondary particles of lithium iron phosphate, thereby better improving the compaction density of the pole piece and improving the processing performance of the pole piece.

[0067] In some embodiments of the present application, the specific surface area of ​​the first positive electrode active material lithium iron phosphate single crystal particles is 6.0 m 2 / g-20m 2 / g, which is beneficial to further reduce the consumption of binder in the pulping process and increase the solid content of the pulp.

[0068] In some embodiments of the present application, the mass percentage of the second positive electrode active material is greater than the mass percentage of the first positive electrode active material. In some embodiments of the present application, the mass percentage of the second positive electrode active material is 55%-90%; in some embodiments of the present application, the mass percentage of the second positive electrode active material is 60%-85%; in some embodiments of the present application, the mass percentage of the second positive electrode active material is 65%-80%.

[0069] When the mass percentage of the second positive electrode active material is greater than the mass percentage of the first positive electrode active material, that is, when the mass percentage of the second positive electrode active material is greater than 50%, a positive electrode sheet with improved performance and lower cost can be obtained. As the content of the second positive electrode active material further increases, the compaction density and processing performance of the sheet are further improved; at the same time, an appropriate amount of the first positive electrode active material needs to be added to fill in the gaps between the lithium iron phosphate secondary particles to increase the bonding force between the lithium iron phosphate secondary particles, improve the compaction density and processing performance of the sheet, improve the electron transmission performance and reduce the membrane resistance. When the mass percentage of the second positive electrode active material is 60%-85%; or further 65%-80%, the first positive electrode active material and the second positive electrode active material work together to improve the comprehensive processing performance of the slurry and the electrical performance of the sheet.

[0070] Positive electrode

[0071] The second aspect of the present application relates to a positive electrode sheet, comprising a positive electrode active material layer, and the positive electrode active material layer contains the positive electrode material of the first aspect of the present application.

[0072] Take the positive electrode sheet of some embodiments of the present application, and use an argon ion beam to cut the sheet perpendicular to the surface of the sheet to expose the cross section of the positive electrode sheet. Figure 3 The scanning electron microscope image of the positive electrode section is shown. Figure 3 It can be seen that the single crystal particles of lithium iron phosphate, the first positive electrode active material, are filled in the particle gaps of the secondary particles of lithium iron phosphate, the second positive electrode active material.

[0073] In some embodiments of the present application, the coating weight per unit area of ​​the single side of the positive electrode sheet is 140 g / m 2 -390g / m 2 In some embodiments of the present application, the coating weight per unit area of ​​the positive electrode sheet is 190 g / m 2 -320g / m 2 In some embodiments of the present application, the coating weight per unit area of ​​the positive electrode sheet is 230 g / m 2 -280g / m 2 .

[0074] The positive electrode sheet provided in the embodiment of the present application has an improved limit solid content of the positive electrode slurry, thereby achieving a higher coating weight and a larger coating thickness; with the increase in coating weight and coating thickness, the battery volume utilization rate is improved, which helps to increase the energy density, but the lithium ion migration path also becomes longer, the diffusion impedance increases, the lithium ion concentration polarization becomes larger during the discharge process of the battery, and the battery capacity is reduced. Therefore, the coating weight can affect the comprehensive performance of the battery energy density and cycle performance.

[0075] In some embodiments of the present application, the diaphragm resistance of the positive electrode sheet is less than 2000mΩ. In some embodiments of the present application, the diaphragm resistance of the positive electrode sheet is less than 800mΩ. In some embodiments of the present application, the diaphragm resistance of the positive electrode sheet is less than 200mΩ. The diaphragm resistance of the positive electrode sheet refers to the overall resistance of the positive electrode sheet after the positive electrode active material layer is provided on the upper and lower surfaces of the positive current collector at room temperature. The positive electrode sheet provided in the embodiments of the present application has the advantages of low diaphragm resistance, high battery cell energy density, and good cycle performance.

[0076] In some embodiments of the present application, the positive electrode sheet includes a positive electrode current collector and the positive electrode active material layer disposed on at least one surface of the positive electrode current collector. The positive electrode active material layer may be disposed on one surface of the positive electrode current collector or on both surfaces of the positive electrode current collector. The positive electrode active material layer contains the positive electrode material of the first aspect of the present application.

[0077] In some embodiments of the present application, the positive electrode active material layer may also include a conductive agent and a binder, wherein the type and content of the conductive agent and the binder are not specifically limited and can be selected according to actual needs. The binder generally includes a fluorinated polyolefin binder. Relative to the fluorinated polyolefin binder, water is generally a good solvent, that is, the fluorinated polyolefin binder generally has good solubility in water. For example, the fluorinated polyolefin binder may include but is not limited to polyvinylidene fluoride (PVDF), vinylidene fluoride copolymers or their modified (for example, carboxylic acid, acrylic acid, acrylonitrile, etc.) derivatives. In the positive electrode active material layer, since the conductivity of the binder itself is poor, the amount of the binder cannot be too high. Optionally, the mass percentage of the binder in the positive electrode active material layer is less than or equal to 2wt% to obtain a lower pole piece impedance. The conductive agent of the positive electrode pole piece may be various conductive agents suitable for lithium ion (secondary) batteries in the art, for example, may be a combination of one or more including but not limited to acetylene black, conductive carbon black, carbon fiber (VGCF), carbon nanotubes (CNT), Ketjen black, etc. The weight of the conductive agent may account for 1 wt% to 10 wt% of the total weight of the positive electrode material layer. Optionally, the weight ratio of the conductive agent to the positive electrode active material in the positive electrode sheet is greater than or equal to 1.5:95.5.

[0078] In some embodiments of the present application, the type of positive electrode current collector is not specifically limited and can be selected according to actual needs. The positive electrode current collector can generally be a layer body, the positive electrode current collector can generally be a structure or part that can collect current, and the positive electrode current collector can be various materials suitable for use as a positive electrode current collector for an electrochemical energy storage device in the art. For example, the positive electrode current collector can include but is not limited to metal foil, and more specifically can include but is not limited to nickel foil and aluminum foil.

[0079] Those skilled in the art may select a suitable method to prepare the positive electrode sheet. For example, the method may include the following steps: mixing the positive electrode active material, binder, and conductive agent of the first aspect of the present application to form a slurry, and then coating the slurry on the positive electrode current collector.

[0080] Lithium secondary battery

[0081] The third aspect of the present application provides a lithium secondary battery, which includes the positive electrode plate described in the second aspect of the present application.

[0082] In some embodiments of the present application, the lithium secondary battery may include a positive electrode sheet, a negative electrode sheet, a separator between the positive electrode sheet and the negative electrode sheet, and an electrolyte. The positive electrode sheet is the positive electrode sheet described in the second aspect of the present application.

[0083] In addition to using the positive electrode sheet described in the second aspect of the present application, the structure and preparation method of the lithium secondary battery of the present application are well known per se.

[0084] In some embodiments of the present application, the negative electrode sheet of the lithium secondary battery generally includes a negative electrode current collector and a negative electrode active material layer located on the surface of the negative electrode current collector, and the negative electrode active material layer generally includes a negative electrode active material. The negative electrode active material can be various materials suitable for negative electrode active materials of lithium secondary batteries in the art, for example, it can be a combination of one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, lithium titanate or other metals that can form alloys with lithium. Among them, the graphite can be selected from a combination of one or more of artificial graphite, natural graphite and modified graphite; the silicon-based material can be selected from a combination of one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, and silicon alloys; the tin-based material can be selected from a combination of one or more of elemental tin, tin oxide compounds, and tin alloys. The negative electrode current collector is generally a structure or part for collecting current, and the negative electrode current collector can be various materials suitable for use as negative electrode current collectors of lithium secondary batteries in the art, for example, the negative electrode current collector can be a metal foil, more specifically, a copper foil. In addition, the negative electrode sheet can also be a lithium sheet.

[0085] In some embodiments of the present application, the isolation membrane of the lithium secondary battery can be various materials suitable for lithium secondary battery isolation membranes in the art, for example, it can be a combination of one or more including but not limited to polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fibers.

[0086] In some embodiments of the present application, the electrolyte of the lithium secondary battery can be various electrolytes suitable for lithium secondary batteries in the art, for example, the electrolyte generally includes an electrolyte and a solvent, the electrolyte generally includes a lithium salt, more specifically, the lithium salt can be an inorganic lithium salt and / or an organic lithium salt, specifically including but not limited to LiPF6, LiBF4, LiN(SO2F)2 (abbreviated as LiFSI), LiN(CF3SO2)2 (abbreviated as LiTFSI), LiClO4, LiAsF6, LiB(C2O4)2 (abbreviated as LiBOB), LiBF2C2O4 (abbreviated as LiDFOB) in one or more combinations. For another example, the concentration of the electrolyte can be 0.8mol / L to 1.5mol / L. The solvent can be any solvent suitable for the electrolyte of a lithium secondary battery in the art. The solvent of the electrolyte is usually a non-aqueous solvent, preferably an organic solvent, and specifically can be a combination of one or more of ethylene carbonate, propylene carbonate, butylene carbonate, pentyl carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate or their halogenated derivatives.

[0087] In some embodiments of the present application, the method for preparing the lithium secondary battery should be known to those skilled in the art. For example, the positive electrode sheet, the isolation membrane and the negative electrode sheet can each be a layer body, so that they can be cut into a target size and stacked in sequence, and can also be wound to a target size to form a battery cell, and can be further combined with an electrolyte to form a lithium secondary battery.

[0088] Figure 4 shows a three-dimensional view of a lithium secondary battery according to a specific embodiment of the present invention, Figure 5 yes Figure 4 An exploded view of a lithium-ion secondary battery is shown. Figure 4 and Figure 5 According to the present application, the lithium secondary battery 5 (hereinafter referred to as the battery cell 5) includes an outer package 51, an electrode assembly 52, a top cover assembly 53 and an electrolyte (not shown). The electrode assembly 52 is accommodated in the housing 51, and the number of the electrode assembly 52 is not limited, and can be one or more.

[0089] It should be noted that Figure 4The battery cell 5 shown is a can-type battery, but the present application is not limited thereto. The battery cell 5 may be a pouch-type battery, that is, the housing 51 is replaced by a metal plastic film and the top cover assembly 53 is eliminated.

[0090] Battery Module

[0091] The fourth aspect of the present application provides a battery module, which includes the lithium secondary battery described in the third aspect of the present application. In some embodiments, the lithium secondary battery can be assembled into a battery module, and the number of lithium secondary batteries contained in the battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module. Figure 6 4 is a perspective view of a battery module 4 as an example. Figure 6 In the battery module 4, the plurality of lithium secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. The plurality of lithium secondary batteries 5 may further be fixed by fasteners. Optionally, the battery module 4 may further include a housing having a storage space, and the plurality of lithium secondary batteries 5 are stored in the storage space.

[0092] Battery Pack

[0093] The fifth aspect of the present application provides a battery pack, which includes the battery module described in the fourth aspect of the present application. In some embodiments, the battery modules can be assembled into a battery pack, and the number of battery modules contained in the battery pack can be adjusted according to the application and capacity of the battery pack. Figure 7 is a three-dimensional diagram of a battery pack 1 as an example, Figure 8 yes Figure 7 Exploded view of the battery pack shown. Figure 7 and Figure 8 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0094] Device

[0095] The sixth aspect of the present application provides a device, which includes the lithium secondary battery described in the third aspect of the present application or the battery module described in the fourth aspect of the present application or the battery pack described in the fifth aspect of the present application, and the lithium secondary battery or the battery module or the battery pack is used as a power source of the device or an energy storage unit of the device. The device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0096] The device can select a lithium secondary battery, a battery module or a battery pack according to its use requirements.

[0097] Fig. 9 A schematic diagram of a device according to a specific embodiment of the present application is shown. The device may be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the device's requirements for high power and high energy density of a lithium-ion secondary battery (i.e., the secondary battery of the present application), a battery pack or a battery module may be used.

[0098] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a lithium-ion secondary battery (ie, the secondary battery of the present application) may be used as a power source.

[0099] Those skilled in the art will appreciate that the various limitations or preferred ranges for component selection, component content, and material physicochemical performance parameters in the electrochemically active materials in the different embodiments of the present application mentioned above can be combined arbitrarily, and the various embodiments obtained by combining them are still within the scope of the present application and are deemed to be part of the disclosure of this specification.

[0100] Unless otherwise specified, the various parameters involved in this specification have common meanings known in the art and can be measured by methods known in the art. For example, the method provided in the embodiments of the present application can be used for testing. In addition, the preferred ranges and options of the various parameters provided in the various preferred embodiments can be combined arbitrarily, and the various combinations obtained are considered to be within the scope of the disclosure of the present application.

[0101] The advantages of the present application are further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present application and are not used to limit the scope of the present application.

[0102] (I) Influence of the parameters of the first active substance and the second active substance on the technical effect of the present application

[0103] Examples 1 to 36, Comparative Examples 1 to 2

[0104] 1. Preparation of positive electrode materials:

[0105] The first positive electrode active material, single crystal lithium iron phosphate, and the second positive electrode active material, secondary particle lithium iron phosphate, are mixed according to a mass percentage ratio to obtain a positive electrode material.

[0106] 2. Preparation of positive electrode sheet:

[0107] The positive electrode material, binder polyvinylidene fluoride (PVDF) and conductive carbon are dry-mixed in a weight ratio of 96.5:2.0:1.5, and an appropriate amount of N-methylpyrrolidone (NMP) solvent is added, and the mixture is fully stirred to form a uniform positive electrode slurry; the slurry is coated on a carbon-coated aluminum foil with a thickness of 13 μm for the positive electrode current collector, and then dried and cold-pressed, and divided into strips for standby use to obtain a positive electrode sheet.

[0108] 3. Obtain the negative electrode sheet, separator, electrolyte and shell according to conventional methods in the art:

[0109] Negative electrode sheet: The negative electrode active material graphite and conductive carbon, binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in a proper amount of water solvent at a weight ratio of 95:3:2 to form a uniform negative electrode slurry; the slurry is coated on the negative electrode current collector Cu foil, and after drying, the electrode sheet is cold pressed to the designed density and separated into strips for later use.

[0110] Isolation film: 12μm PP isolation film is used.

[0111] Electrolyte: Use lithium iron phosphate general electrolyte.

[0112] Shell: The shell material is made of aluminum-plastic film.

[0113] 4. Preparation of lithium secondary batteries:

[0114] The positive electrode sheet, the separator, and the negative electrode sheet are wound to form a bare cell, which is then encapsulated with an aluminum-plastic film, injected with electrolyte, and subjected to formation, exhaust, and high-temperature aging to obtain a lithium secondary battery.

[0115] The relevant parameters of the positive electrode materials, the performance of the positive electrode sheets and the lithium secondary batteries in Examples 1 to 36 and Comparative Examples 1 to 2 can be tested by conventional methods in the art. The following are examples of the testing methods:

[0116] 1. BET specific surface area of ​​the first positive electrode active material:

[0117] The specific surface area tester is used for testing, and the testing instrument model is: tristar 3020. The testing steps are briefly described as follows: take 2.0g-4g of the first positive electrode active material sample; put the sample into a sample tube, put it into a heating bag, and degas it (degassing conditions are 200°C, 2 hours); after degassing, when the temperature of the degassing station drops to room temperature, remove the sample tube from the degassing station, weigh and calculate the total mass of the sample; put the sample tube into the test filling rod, perform BET test, and obtain the test results.

[0118] 2. Median particle size Dv50 of the first positive electrode active material:

[0119] Measuring instrument: laser particle size analyzer; equipment model: Malvern Mastersizer 2000E or Mastersizer 3000. Because the angle of scattered light of the particles of the positive electrode material is inversely proportional to the diameter of the particles under the irradiation of the laser beam, and the scattered light intensity decays logarithmically with the increase of the angle, the energy distribution of the scattered light is directly related to the distribution of the particle diameter. By receiving and measuring the energy distribution of the scattered light, the particle size distribution characteristics of the particles can be obtained. The solvent used for the test can be water or other organic solvents used to prepare the slurry, and the sample is dispersed by ultrasound. The obtained analysis result Dv50 means that the diameter of the particles accounting for 50% of the total volume is greater than this value, and the diameter of the particles accounting for 50% of the total volume is less than this value.

[0120] 3. Powder resistivity of the first positive electrode active material at 12Mpa:

[0121] Dry the first positive electrode active material powder, weigh an appropriate amount of powder, and use a powder resistivity tester, equipment model Suzhou Jingge ST2722 or Sansi Zongheng UTM7305. Place the dry powder sample in the mold / sample bin of the resistivity tester, the sample bin depth is 20mm, and the cross-sectional area is 1cm 2 , then slowly apply pressure from small to large, manually collect data, and record the corresponding powder resistivity test results at different pressure points.

[0122] 4. Median particle size Dv50 of the second positive electrode active material:

[0123] The detection was performed according to the detection method of the median particle size Dv50 of the first positive electrode active material.

[0124] 5. BET specific surface area of ​​the second positive electrode active material:

[0125] The specific surface area of ​​the first positive electrode active material was measured by referring to the BET measurement method.

[0126] 6. The membrane resistance of the positive electrode:

[0127] The ACCFLM diaphragm resistance test system of Hangzhou Chuanyuan Technology Co., Ltd. was used to detect the overall diaphragm resistance of the positive electrode sheet (positive electrode active material layer is set on both sides) in the implementation of the present application by adopting the double probe method.

[0128] 7. Detection of bonding strength between membrane and current collector:

[0129] Take the positive electrode to be tested, and use a blade to cut a sample with a width of 30mm and a length of 100-160mm; at the same time, stick the double-sided tape on the steel plate, with a width of 20mm and a length of 90-150mm. Stick the cut electrode sample on the double-sided tape with the test side facing down. Insert a paper tape with a width equal to the electrode and a length greater than the sample length of 80-200mm under the electrode, and fix it with wrinkle glue, then use a Sansi tensile machine to test the bonding strength of the membrane and the current collector.

[0130] 8. Gram capacity:

[0131] The gram capacity of 1 / 3C at 25°C is used to characterize the capacity utilization of the battery. The specific test process is briefly described as follows: (1) Place the battery in a 25°C oven environment and let it stand for 2 hours until the battery temperature remains at 25°C; (2) 1 / 3C DC to 2.0V; (3) Pause for 5 minutes; (4) 1 / 3C CC to 3.65V and CV to I≤0.05C; (5) Pause for 5 minutes; (6) 1 / 3C DC to 2.0V. This step is the actual battery cell test capacity. Combined with the mass of the positive electrode active material, the gram capacity utilization can be calculated.

[0132] 9. Cycle performance test:

[0133] The 1C / 1C cycle at 60°C is used to detect the number of cycles when the battery capacity decays to 80% of the initial value. The specific process is briefly described as follows: (1) Place the battery in a 45°C oven and let it stand for 2 hours until the battery temperature remains at 25°C; (2) Charge at 1C constant current to 3.65V, and continue constant voltage charging until the charging current is less than 0.05C; (3) Pause for 5 minutes; (4) Discharge at 1C constant current to 2.5V; (5) Pause for 5 minutes. Steps (2) to (6) are one charge and discharge cycle of the battery. Repeat steps (2) to (6) until the number of cycles when the battery capacity decays to 80% of the initial value is reached.

[0134] The relevant parameters of the positive electrode materials of Examples 1 to 36 and Comparative Examples 1 to 2 are shown in Table 1.

[0135] Table 1

[0136]

[0137] The performance test results of Examples 1 to 36 and Comparative Examples 1 to 2 are shown in Table 2.

[0138] Table 2

[0139]

[0140] Data Discussion:

[0141] (1) Examples 1 to 36, Comparative Examples 1 to 2:

[0142] The positive electrode material of Comparative Example 1 only contains lithium iron phosphate single crystal particles. From the test data in Table 2, it can be seen that the processing performance of the positive electrode plate of Comparative Example 1 is poor, which is specifically manifested in that the limit solid content of the positive electrode material slurry is very low, the cracking of the plate after coating is serious, and the bonding force between the membrane and the current collector is low. At the same time, the capacity and cycle performance of the lithium secondary battery of Comparative Example 1 are not good.

[0143] The positive electrode material of Comparative Example 2 only contains lithium iron phosphate secondary particles. From the data in Table 2, it can be seen that for the positive electrode plate of Comparative Example 2, although the maximum solid content of the slurry is greatly improved and the cracking of the plate after coating is improved, the bonding force between the membrane and the current collector is very low, and the membrane resistance of the positive electrode plate is relatively high, and the capacity utilization and cycle performance of the battery are also not ideal.

[0144] The positive electrode materials of Examples 1 to 36 include lithium iron phosphate single crystal particles and lithium iron phosphate secondary particles. Compared with Comparative Examples 1 and 2, the processing performance of the positive electrode plates of Examples 1 to 36 is generally improved, the limit solid content of the positive electrode slurry is relatively high, the cracking of the plate after thick coating is improved, and the bonding force between the diaphragm and the current collector is improved, the diaphragm resistance is reduced, and the battery capacity and cycle performance are better than those of Comparative Examples 1 and 2.

[0145] In addition, it can be seen from Examples 1 to 5 that the positive electrode materials obtained by mixing lithium iron phosphate secondary particles and lithium iron phosphate single crystal particles doped with different elements can achieve the effects of improving the processing performance of the electrode sheet and improving the capacity and cycle performance of the battery; among them, Ti element doping has the most significant effect on improving the capacity and cycle performance of the battery cell, and the optimal doping amount of Ti element in the positive electrode material is 2000ppm.

[0146] (2) Embodiments 5 to 9:

[0147] Examples 5 to 9 show the change in powder resistivity of lithium iron phosphate single crystal particles at 12 MPa in the positive electrode material provided by the present application, and the effect on the electrode processing performance and battery performance.

[0148] The powder resistivity of the first positive electrode active material, lithium iron phosphate single crystal particles, under 12Mpa is less than 150Ω·cm, or less than 80Ω·cm, or further less than 30Ω·cm. As the powder resistivity of the lithium iron phosphate single crystal particles decreases, its conductivity is improved, and the electron transfer performance between the positive electrode active materials is better, so that the membrane resistivity of the positive electrode sheet is reduced, which is beneficial to the capacity and cycle performance of the battery.

[0149] (3) Embodiments 5, 10 to 17:

[0150] Examples 5 and 10 to 17 show the effect of changes in the median particle size Dv50 of lithium iron phosphate secondary particles in the positive electrode material provided in the present application on the electrode sheet processing performance and battery performance.

[0151] When the median particle size Dv50 of the lithium iron phosphate secondary particles is less than 2.5μm, the specific surface area of ​​the secondary particles is large, resulting in enhanced liquid absorption, which may cause slight cracking during the drying process of the membrane; at the same time, the uniformity of the conductive carbon distribution of the active material layer after coating is insufficient, which increases the resistance of the membrane. When the median particle size Dv50 of the lithium iron phosphate secondary particles is greater than 10.5μm, the sufficiency of the first positive electrode active material filling in the gap between its particles is weakened, which is not conducive to the improvement of the compaction density of the pole piece, and also affects the flatness of the contact layer between the active material and the current collector, resulting in the contact between the active material and the current collector being affected, which in turn increases the probability of the pole piece breaking during processing. When the Dv50 of the lithium iron phosphate secondary particles is 6μm-7μm, the pole piece processing performance is better, and the bonding force between the membrane and the current collector is also better, which is conducive to the battery capacity and cycle performance to reach the best state.

[0152] (4) Embodiments 5, 18 to 25:

[0153] Examples 5 and 18 to 25 show the effect of changes in the specific surface area BET of lithium iron phosphate secondary particles in the positive electrode material provided in the present application on the electrode processing performance and battery performance.

[0154] When the BET specific surface area of ​​lithium iron phosphate secondary particles is less than 3.5 m 2 / g, the electrochemical reaction activity of lithium secondary batteries is low, which affects the cycle performance of the battery to a certain extent. When the BET specific surface area of ​​lithium iron phosphate secondary particles is higher than 10.5m 2 / g, the effect of increasing the solid content of the positive electrode slurry and improving the processing performance of the electrode sheet becomes less obvious. When the specific surface area of ​​the lithium iron phosphate secondary particles is 6.5m 2 / g-7.5m 2 / g, it can not only significantly increase the solid content of the positive electrode slurry and improve the processing performance of the electrode sheet, but also ensure the electrochemical reaction activity of the battery, making the improvement of the battery capacity and cycle performance more obvious.

[0155] (5) Embodiments 5, 26 to 30:

[0156] Examples 5 and 26 to 30 show the effect of the change in the average particle size of the primary particles agglomerated to form lithium iron phosphate secondary particles in the positive electrode material provided by the present application on the electrode sheet processing performance and battery performance.

[0157] When the average particle size d of the primary particles is in the range of 20nm-500nm, the particle size of the primary particles is in the appropriate range, the side reaction rate between the positive electrode material and the electrolyte and the kinetic performance of the positive electrode of the battery are at a reasonable level, and the battery capacity and cycle performance are better. When the average particle size d of the primary particles is less than 20nm, the side reaction rate between the positive electrode material and the electrolyte is large, which is beneficial to the initial capacity of the positive electrode material, but the battery cycle performance is not high. When the average particle size d of the primary particles is greater than 500nm, the processability of the positive electrode slurry and the compaction density of the positive electrode sheet are improved, but the kinetic performance of the positive electrode of the battery is reduced, resulting in a decrease in the battery capacity.

[0158] (6) Embodiments 5, 31 to 36:

[0159] Examples 5 and 31 to 36 show the effects of changes in the mass percentage of lithium iron phosphate secondary particles and lithium iron phosphate single crystal particles in the positive electrode material provided by the present application on the electrode sheet processing performance and battery performance.

[0160] The lithium iron phosphate secondary particles have a low specific surface area, which can increase the solid content of the slurry, reduce the difficulty of processing thick coated pole pieces, and reduce the production cost of positive electrode materials; and the lithium iron phosphate single crystals are filled in the particle gaps of the lithium iron phosphate secondary particles, further increasing the compaction density of the pole piece and improving the processing performance of the pole piece. When the mass percentage of the second positive electrode active material is greater than the mass percentage of the first positive electrode active material, that is, when the mass percentage of the second positive electrode active material is greater than 50%, a positive electrode pole piece with improved performance and lower cost can be obtained. As the content of the second positive electrode active material further increases, the compaction density and processing performance of the pole piece are further improved; at the same time, an appropriate amount of the first positive electrode active material needs to be added to fill in the gaps between the lithium iron phosphate secondary particles to increase the bonding force between the lithium iron phosphate secondary particles, improve the compaction density and processing performance of the pole piece, improve the electron transmission performance and reduce the membrane resistance. When the mass percentage of the second positive electrode active material is 60%-85%; or further 65%-80%, the first positive electrode active material and the second positive electrode active material synergize with each other to improve the comprehensive processing performance of the slurry and the electrical performance of the electrode sheet.

[0161] (II) Effect of coating weight per unit area on a single side of the positive electrode sheet on the technical effect of the present application

[0162] Embodiments 37 to 44

[0163] In Examples 37 to 44, the method for preparing positive electrode materials and lithium secondary batteries is basically the same as that in Example 5, the only difference being that the coating weight on one side of the positive electrode sheet is changed.

[0164] In addition, for the positive electrode sheets and lithium secondary batteries in Examples 37 to 44, in addition to the same performance tests as in Examples 1 to 36, the energy density of the lithium secondary batteries was also tested.

[0165] The detection method of energy density of lithium secondary battery is as follows: (1) Place the battery in a 25℃ oven environment and let it stand for 2h until the battery temperature remains at 25℃; (2) 1 / 3C DC to 2.0V; (3) Pause for 5min; (4) 1 / 3C CC to 3.65V and CV toI≤0.05C; (5) Pause for 5min; (6) 1 / 3C DC to 2.0V. This step is the actual battery cell test capacity. Combined with the mass of the positive electrode active material, the gram capacity can be calculated. The battery cell energy can be calculated by integrating the voltage-capacity curve, energy value / battery cell weight value = energy density.

[0166] The relevant parameters of the positive electrode materials of Examples 37 to 44 are shown in Table 3.

[0167] Table 3

[0168]

[0169] The performance test results of the positive electrode sheets and lithium secondary batteries of Examples 37 to 44 are shown in Table 4.

[0170] Table 4

[0171]

[0172] Data Discussion:

[0173] Examples 37 to 44 show the influence of the coating weight per unit area on a single side of the positive electrode sheet on the technical effect of the present application.

[0174] The positive electrode material provided in this application can be used to prepare a positive electrode slurry with a high solid content, and further obtain a pole piece with a high coating weight and a high coating thickness. With the increase of coating weight and coating thickness, the volume utilization rate of the battery is improved, which helps to improve the energy density, but the lithium ion migration path also becomes longer, the diffusion impedance increases, and the lithium ion concentration polarization of the battery during discharge becomes larger but decreases. When the coating weight is 230g / m 2 -280g / m 2 When the battery is charged, the energy density and cycle performance of the battery are optimal.

[0175] According to the disclosure and teaching of the above description, those skilled in the art may also make changes and modifications to the above implementation. Therefore, the present application is not limited to the specific implementation disclosed and described above, and some modifications and changes to the present application should also fall within the scope of protection of the claims of the present application. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present application.

Claims

1. A positive electrode material, characterized in that: The invention comprises a first positive electrode active material represented by formula (I) and a second positive electrode active material represented by formula (II), LiFe 1-x1 M1 x1 PO4(I) LiFe 1-x2 M2 x2 PO4(II) Wherein, 0≤x1≤0.1, 0≤x2≤0.1, M1 and M2 are each independently selected from at least one of Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr or Ti; The first positive electrode active material is a single crystal particle, and the second positive electrode active material is a secondary particle; the specific surface area of ​​the second positive electrode active material is 3.5 m 2 / g-10.5m 2 / g.

2. The positive electrode material according to claim 1, characterized in that The secondary particles are in a pomegranate-like shape formed by agglomeration of a plurality of primary particles.

3. The positive electrode material according to claim 2, characterized in that The primary particles are single crystal nanoparticles.

4. The positive electrode material according to claim 2, characterized in that The particle size d of the primary particles is in the range of 20 nm to 500 nm.

5. The positive electrode material according to claim 1 or 2, characterized in that: The median particle size Dv50 of the second positive electrode active material is 2.5 μm-10.5 μm.

6. The positive electrode material according to claim 1 or 2, characterized in that: The second positive electrode active material satisfies at least one of the following conditions: (1) The median particle size Dv50 of the second positive electrode active material is 4.5 μm-8.5 μm; (2) The specific surface area of ​​the second positive electrode active material is 5 m 2 / g-9m 2 / g.

7. The positive electrode material according to claim 1 or 2, characterized in that: The second positive electrode active material satisfies at least one of the following conditions: (1) The median particle size Dv50 of the second positive electrode active material is 6 μm-7 μm; (2) The specific surface area of ​​the second positive electrode active material is 6.5 m 2 / g-7.5m 2 / g.

8. The positive electrode material according to claim 1, characterized in that The single crystal particles are independent particles with continuous internal lattices and almost no grain boundary separation.

9. The positive electrode material according to claim 1 or 4, characterized in that: The powder resistivity of the first positive electrode active material at 12 MPa is less than or equal to 150 Ω·cm.

10. The positive electrode material according to claim 1 or 4, characterized in that: The powder resistivity of the first positive electrode active material at 12 MPa is 80 Ω·cm or less.

11. The positive electrode material according to claim 1 or 4, characterized in that: The powder resistivity of the first positive electrode active material at 12 MPa is less than or equal to 30 Ω·cm.

12. The positive electrode material according to any one of claims 1 to 4, characterized in that: The first positive electrode active material satisfies at least one of the following conditions: (1) The median particle size Dv50 of the first positive electrode active material is 0.5 μm-2.0 μm; (2) The specific surface area of ​​the first positive electrode active material is 6.0 m 2 / g-20m 2 / g.

13. The positive electrode material according to any one of claims 1 to 4, characterized in that: The mass percentage of the second positive electrode active material is greater than the mass percentage of the first positive electrode active material.

14. The positive electrode material according to any one of claims 1 to 4, characterized in that: The mass percentage of the second positive electrode active material is 55%-90%.

15. The positive electrode material according to any one of claims 1 to 4, characterized in that: The mass percentage of the second positive electrode active material is 60%-85%.

16. The positive electrode material according to any one of claims 1 to 4, characterized in that: The mass percentage of the second positive electrode active material is 65%-80%.

17. A positive electrode sheet, comprising a positive electrode active material layer, characterized in that: The positive electrode active material layer contains the positive electrode material according to any one of claims 1 to 16.

18. The positive electrode sheet according to claim 17, characterized in that: The coating weight per unit area of ​​the positive electrode sheet is 140 g / m 2 -390g / m 2 .

19. The positive electrode sheet according to claim 17, characterized in that: The coating weight per unit area of ​​the positive electrode sheet is 190 g / m 2 -320g / m 2 .

20. The positive electrode sheet according to claim 17, characterized in that: The coating weight per unit area of ​​the positive electrode sheet is 230 g / m 2 -280g / m 2 .

21. The positive electrode sheet according to any one of claims 17 to 20, characterized in that: The film resistance of the positive electrode plate is less than 2000mΩ.

22. The positive electrode sheet according to any one of claims 17 to 20, characterized in that: The membrane resistance of the positive electrode plate is less than 800 mΩ.

23. The positive electrode sheet according to any one of claims 17 to 20, characterized in that: The film resistance of the positive electrode plate is less than 200 mΩ.

24. A lithium secondary battery, characterized in that: Comprising a positive electrode sheet according to any one of claims 17-23.

25. A battery module, characterized in that: Comprising the lithium secondary battery according to claim 24.

26. A battery pack, characterized in that: Comprising the battery module according to claim 25.

27. An electrical device, characterized in that: It includes the lithium secondary battery according to claim 24, the battery module according to claim 25, or the battery pack according to claim 26, and the lithium secondary battery, the battery module, or the battery pack is used as a power source for the electric device or an energy storage unit for the electric device.

Citation Information

Patent Citations

  • Cathode material and preparation method thereof and lithium-ion battery

    CN105185982A

  • Lithium-ion battery and cathode active material for same

    CN109309227A